R-M and M-R Model for Interpreting Logic State of Memristor Aided NOR with Enhanced Noise Margin - Shalini Singh; Shyam Akashe (Recent Trends in Mathematics, 2024)
Memristive crossbar arrays are one of the fascinating subjects in the field of nanoelectronics and memory devices. The arrangement of arrays consists of grid-like structure with rows and columns of memristors which are resistive devices that can preserve their resistance state even after power is turned OFF. They have now emerged as a promising alternative to traditional memory technologies due to their high density, non-volatility and low power consumption. This paper presents the technique of reading the state of memristor via two different models M-R model and R-M model in Memristor Aided Logic (MAGIC) NOR gate for prime and optimum noise margin. A comparative analysis of both the models are presented in which the M-R model is found to be more beneficial with 5% maximum voltage drop which is a bearable range for any voltage divider. Additionally, the study presents a thorough methodology for determining noise margins in order to assess the dependability and stability of logic circuits. The resilience of memristor-based logic devices in practical applications is determined by this analysis, which guarantees performance under a range of operating situations.
Keywords: Magic NOR; Memristor; Model; Noise Margin; Voltage divider; memory